TEKNO KLEM: NEW DISPOSABLE DEVICE FOR PEDIATRIC CIRCUMCISION–A CASE REPORT - Yuri, Prahara; Darsono; Indrasyafrudin, Anwar (Indonesian Urological Association, 2026)
Objective: This case report aimed to present the use of Tekno Klem, a novel disposable circumcision device. Unlike existing devices, Tekno Klem allows immediate clamp removal, potentially reducing the risk of postoperative complications. Case(s) Presentation: A 6-year-old boy presented to the Urology Outpatient Clinic with difficulty in retracting the foreskin of the penis. Physical examination revealed a non-retractable foreskin with a constrictive ring, classified as grade 3 phimosis. Elective dorsal slit surgery using Tekno Klem device was scheduled. The circumcision procedure using the Tekno Klem device began with measuring the glans size to ensure appropriate device selection. The appropriate Tekno Klem clamp size was selected from the available options: 12 mm, 14 mm, 16 mm, 18 mm, 22 mm, and 27 mm. The preputial skin was marked to define the excision area. The safety tube was then carefully positioned around the glans. Subsequently, the clamp frame was inserted. Once the desired positioning was confirmed, the screw cap was applied, locking the clamp securely in place through its serrated and threaded mechanism. The preputial skin was excised using thermal cautery. After clamp removal, N-butyl cyanoacrylate ointment was applied to protect the wound. The procedure lasted 15 minutes. Discussion: Postoperative pediatric penile perception scored 10, indicating improved penile appearance, while voiding satisfaction scored 5, reflecting favorable functional outcomes. No complications, including bleeding, hematoma, infection, glans injury, meatal stenosis, or delayed healing, were observed. The circumcision site healed properly with satisfactory cosmetic and functional results. Conclusion: Tekno Klem offers enhanced precision, safety, and ease of use over conventional devices, with the potential to reduce complications and optimize outcomes, particularly in settings prioritizing surgical accuracy and patient safety. Keywords: Tekno Klem, circumcision, disposable, pediatric, clamp.